Canine pododermatitis: A retrospective study of 300 cases - Bouza- Rapti, P; Kaltsogianni, F; Koutinas, AF; Farmaki, R (Journal of the Hellenic Veterinary Medical Society, 2023)
The medical records of 300 dogs with pododermatitis were reviewed and the possible associations between signalment, history, clinical and laboratory findings, and various primary and secondary causative factors were investigated. The age of the dogs ranged from 3 months to 15 years. Mongrels, West Highland White Terriers (WHWTs) , French Bulldogs, German Shepherd Dogs (GSDs) and Shar-Peis were overrepresented. In most of the cases pododermatitis was chronic/recurrent (69%), pruritic (75%) and affected all four feet (54%). The dominant affected site was interdigital skin (66%), whereas erythema (77.7%), hypotrichosis/alopecia (57%), skin thickness (26.3%), crusts (25%) and hyperpigmentation (22%) were the most frequently encountered lesions. Bacteria (109/300), as secondary causes, were more commonly found than Malassezia spp. (43/300). The principal primary causes were allergies (131/300), pododemodicosis (32/300), sarcoptic mange (17/300), skin neoplasms (14/300), leishmaniosis (14/300) and interdigital furunculosis (11/300). In this study, West Highland White Terriers, Shar-Peis and French Bulldogs were predominantly presented with allergic pododermatitis (P=0.001). Interdigital skin was the overrepresented site for atopic dermatitis (117/131) and pododemodicosis (20/32), while metatarsal area was for sarcoptic mange (17/17). Crusts were commonly seen in bacterial pododermatitis (P<0.001), whereas greasy crusts (P<0.001) and lichenification (P=0.008) were seen in Malassezia pododermatitis. Finally, dogs that did not often have paw cleaning had the lowest rates of Malassezia infection (P=0.047).